Structural and Functional Abnormalities in the Olfactory System of Fragile X Syndrome Models - Bodaleo, Felipe; Tapia-Monsalves, Carola; Cea-Del Rio, Christian; Gonzalez-Billault, Christian; Nunez-Parra, Alexia (Frontiers in Molecular Neuroscience, 2019)
Fragile Syndrome X (FXS) is the most common inherited form of intellectual disability. It is produced by mutation of the Fmr1 gene that encodes for the Fragile Mental Retardation Protein (FMRP), an important RNA-binding protein that regulates the expression of multiple proteins located in neuronal synapses. Individuals with FXS exhibit abnormal sensory information processing frequently leading to hypersensitivity across sensory modalities and consequently a wide array of behavioral symptoms. Insects and mammals engage primarily their sense of smell to create proper representations of the external world and guide adequate decision-making processes. This feature in combination with the exquisitely organized neuronal circuits found throughout the olfactory system and the wide expression of FMRP in brain regions that process olfactory information makes it an ideal model to study sensory alterations in FXS models. In the last decade several groups have taken advantage of these features and have used the olfactory system of fruit fly and rodents to understand neuronal alteration giving rise to sensory perception issues. In this review we will discuss molecular, morphological and physiological aspects of the olfactory information processing in FXS models. We will highlight the decreased inhibitory/excitatory synaptic balance and the diminished synaptic plasticity found in this system resulting in behavioral alteration of individuals in the presence of odorant stimuli.